2021
DOI: 10.1093/jbcr/irab061
|View full text |Cite
|
Sign up to set email alerts
|

Using Pressure Mapping to Optimize Hospital-Acquired Pressure Injury Prevention Strategies in the Burn Intensive Care Unit

Abstract: Although prior studies have demonstrated the utility of real-time pressure mapping devices in preventing pressure ulcers, there has been little investigation of their efficacy in burn intensive care unit (BICU) patients, who are at especially high risk for these hospital-acquired injuries. This study retrospectively reviewed clinical records of BICU patients to investigate the utility of pressure mapping data in determining the incidence, predictors and associated costs of hospital-acquired pressure injuries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Besides, using equipment to reduce pressure and shear is recommended by current guidelines and manual repositioning can be time‐consuming and even result in work‐related musculoskeletal disorders 47 . A interface pressure monitoring can increase efficiency of repositioning and visual feedback provided by pressure mapping also improve proficiency in preventative repositioning 48 . However, relevant equipment such as turning device and pressure mapping were not observed as being available for nurses in our study.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Besides, using equipment to reduce pressure and shear is recommended by current guidelines and manual repositioning can be time‐consuming and even result in work‐related musculoskeletal disorders 47 . A interface pressure monitoring can increase efficiency of repositioning and visual feedback provided by pressure mapping also improve proficiency in preventative repositioning 48 . However, relevant equipment such as turning device and pressure mapping were not observed as being available for nurses in our study.…”
Section: Discussionmentioning
confidence: 81%
“… 47 A interface pressure monitoring can increase efficiency of repositioning and visual feedback provided by pressure mapping also improve proficiency in preventative repositioning. 48 However, relevant equipment such as turning device and pressure mapping were not observed as being available for nurses in our study.…”
Section: Discussionmentioning
confidence: 87%
“…Therefore, their value in high-risk ICU patients remain often uncertain. Nevertheless, there are two areas where advances in ICU-acquired PI prevention have been made: continuous bedside pressure mapping (CBPM) [ 9 , 10 ] and prophylactic dressing use [ 11 , 12 ].…”
Section: Knowledge Gains and Prevention Improvementsmentioning
confidence: 99%
“…Reports from a randomized trial showed a reduced ICU-acquired PI rate with use of CBPM [ 9 ]. Similarly, following the introduction of CBPM, another study showed a reduction in not only the number of ICU-acquired PIs but also the severity of PIs resulting in significant cost savings [ 10 ].…”
Section: Knowledge Gains and Prevention Improvementsmentioning
confidence: 99%
See 1 more Smart Citation